Pengaruh Manajemen Koperasi Terhadap Minat Beli Santri Pondok Pesantren Riyadhul Mutafakkirin Rangkasbitung Lebak Banten - Yunia, Noorma (e-Jurnal Aksioma Al-Musaqoh : Journal of Islamic Economics and Business Studies, 2024)
The progress of the business world in Indonesia has resulted in the importance of entrepreneurial spirit education being implemented in Islamic boarding schools. Entrepreneurship is a process of a person's ability to observe and assess a business opportunity, take a profit action by gathering existing resources. Cooperatives as one of the original life veins of the Indonesian nation need to be preserved and developed in order to support the economy of the community at large. This study was conducted with the aim of obtaining data on the management of the Riyadhul Mutafakkirin Islamic Boarding School women's cooperative, obtaining data on santri buying interest in the Riyadhul Mutafakkirin Islamic Boarding School women's cooperative and analyzing whether there is an influence of cooperative management carried out by the Riyadhul Mutafakkirin Islamic Boarding School cooperative on santri buying interest using simple linear regression data analysis techniques using the SPSS V.22 program. The method used in the research is quantitative descriptive statistics with the population, namely students of the Riyadhul Mutafakkirin Islamic Boarding School with a sample of 35 respondents. Data collection was obtained through primary data in the form of a questionnaire. Based on the results of data processing that researchers get in the field, the data shows that cooperative management has a positive and significant influence on the buying interest of Riyadhul Mutafakkirin Islamic Boarding School students with the results of the t test which shows the t value of 27.311> from the t table, namely 2.034. So that the independent variable, namely cooperative management, has an effect on the dependent variable, namely buying interest and the significance is 0.000 <0.05. So that the independent variable, namely cooperative management, has an effect on the dependent variable, namely buying interest and the significance is 0.000 <0.05. So that thus Ho is rejected and Ha is accepted.